Diasporic Africa and its contexts: Which texts are considered art and lite rature and in what context? (Olhares, 2025)
In a preliminary proposal, this article has the exploratory nature of thinking about which space literature’s is inserted in literature in the classroom in terms of art. Based on the African expressiveness adressed by Asante (2014), and Martins (2021) and their multiplicities, we propose to reflect in the classroom what the outline of what it’s called African literature or African diasporic literature and its possible developments in different artistics languages. To project this reflection we used and application of Law n° 10.639, which refers to the obligation of African-Brazilian history and culture in the school context.
Keywords: African Literature; Cultural Mediation; The law n° 10.639